2015
DOI: 10.1261/rna.052449.115
|View full text |Cite
|
Sign up to set email alerts
|

Control of mRNA decapping by positive and negative regulatory elements in the Dcp2 C-terminal domain

Abstract: Decapping commits an mRNA to complete degradation and promotes general 5 ′ to 3 ′ decay, nonsense-mediated decay (NMD), and transcript-specific degradation. In Saccharomyces cerevisiae, a single decapping enzyme composed of a regulatory subunit (Dcp1) and a catalytic subunit (Dcp2) targets thousands of distinct substrate mRNAs. However, the mechanisms controlling this enzyme's in vivo activity and substrate specificity remain elusive. Here, using a genetic approach, we show that the large C-terminal domain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
139
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(152 citation statements)
references
References 53 publications
10
139
0
Order By: Relevance
“…Competition is nevertheless possible as the local concentrations of Xrn1, Pat1, and Dhh1 are very high in processing bodies and as the EVH1:PRS affinity will be enhanced by avidity effects that arise due to the presence of multiple PRS within the IDRs and due to additional interactions between the decapping factors and the decapping machinery. In line with that, it was recently shown that the in vivo activity of the S. cerevisiae Dcp1:Dcp2 decapping enzyme increases in a gradual manner upon a stepwise shortening of the C-terminal tail of Dcp2 (He and Jacobson 2015). Here, we show that the Dcp2 C-terminal tail contains a number of PRS that can interact in cis with the Dcp1 aromatic groove.…”
Section: Discussionsupporting
confidence: 87%
“…Competition is nevertheless possible as the local concentrations of Xrn1, Pat1, and Dhh1 are very high in processing bodies and as the EVH1:PRS affinity will be enhanced by avidity effects that arise due to the presence of multiple PRS within the IDRs and due to additional interactions between the decapping factors and the decapping machinery. In line with that, it was recently shown that the in vivo activity of the S. cerevisiae Dcp1:Dcp2 decapping enzyme increases in a gradual manner upon a stepwise shortening of the C-terminal tail of Dcp2 (He and Jacobson 2015). Here, we show that the Dcp2 C-terminal tail contains a number of PRS that can interact in cis with the Dcp1 aromatic groove.…”
Section: Discussionsupporting
confidence: 87%
“…Maximal in vitro activation of Upf1’s ATPase and helicase activities requires both Upf2 and Upf3 (30). The CH domain of yeast Upf1 binds to the C-terminal region of Upf2 (78), the ribosomal protein Rps26 (153), and the decapping enzyme subunit Dcp2 (80, 82), and also self-associates (79), suggesting that it may play a role in sequential molecular interactions during execution of NMD. Metazoan Upf1 contains extra conserved extensions at both its N and C termini.…”
Section: The Nonsense-mediated Decay Machinerymentioning
confidence: 99%
“…EDC3 (CFY25), PAT1 (SYY2674), LSM1 (SYY2680), and DHH1 (SYY2686) were described in He and Jacobson (2015a). A strain harboring a deletion of SCD6 (SSY2352) was constructed by gene replacement (Guthrie and Fink 1991) using a DNA fragment harboring the scd6::KanMX6 null allele.…”
Section: Yeast Strainsmentioning
confidence: 99%
“…These three proteins interact with each other, the ribosome, and multiple translation and mRNA decay factors (Kervestin and Jacobson 2012). Based on these molecular interactions, several potential functions have been proposed for the Upf factors, including remodeling terminating mRNPs (Franks et al 2010), releasing and recycling ribosomal subunits (Ghosh et al 2010), and recruiting mRNA decay factors (Okada-Katsuhata et al 2012;Nicholson et al 2014;He and Jacobson 2015a). However, the exact roles for the Upfs, and their modes of action in NMD, remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%